Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.